PUBLIC EDUCATION ABOUT EYES DURING THE COVID-19 PANDEMIC - Ramzi Amin; Petty Purwanita; Prima Maya Sari (Fakultas Kedokteran Universitas Sriwijaya, 2021)
In December 2019, a case of pneumonia of unknown etiology first reported in Wuhan, Hubei Province, China. (1) The etiology was finally identified and showed a new type of coronavirus, which was given the tentative name 2019 novel coronavirus (2019-nCoV). On February 11, 2020, the World Health Organization (WHO) announced the name of the new virus, namely Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), and the name of the disease as Coronavirus Disease (COVID-19).Indonesia reported its first two confirmed cases of COVID-19 inMarch 2, 2020. As of September 8, 2020, the number of confirmed cases of COVID-19 in Indonesia was 200,035, with 8,230 deaths (CFR 6.9%).